187k views
1 vote
-15x + 20y = 15
0=18x + 24y - 18

User Cinsere
by
5.7k points

1 Answer

0 votes

Answer:

Explanation:

given:

-15x + 20y =15

0 = 18x + 24y -18

let's get the 2nd equation into a form like the top equation

-18x -24y = -18

multipy thur by -1

18x +24y = 18

we'll need to use substitution for this problem. elimination has a zero issue.

18x = -24y +18

x = -
(4)/(3) y + 1

now plug this into the 1st equation

-15( -
(4)/(3) y + 1 ) + 20 y = 15

20y -15 +20y = 15

40y = 30

y = 3/4

now that we've found y, plug that into our x = -
(4)/(3) y + 1 , to find x

x = -1 +1

x = 0

User Jake Kalstad
by
5.5k points